(untitled) (Altre Modernità, 2024)
The concept of "narrative competence," developed by Rita Charon since 2000 to describe healing through storytelling, is an emerging model in Western medicine. In this article, we examine forms of narrating/healing that transcend the binary and hierarchical relationships between doctor and "the others" (patients, colleagues, society) on which Charon’s model is based. Our focus is on the literary-activist work of the Colectiva Editorial Hermanas en la Sombra, a feminist solidarity collective composed of both free and imprisoned women in Morelos (Mexico), whose goal is to dignify incarcerated women through writing and publishing collective books. Drawing on Marcela Lagarde’s concept of sorority or sisterhood as a political gender pact between women united through difference, we explore some of the new feminist forms that emerge from a decolonial narrative practice that challenges the category of the (feminised) "Other," as well as many other colonial-patriarchal stereotypes. We analyze Los sueños de una cisne en el pantano (The Dreams of a Swan in the Swamp, 2016) by Leo Zavaleta, a woman of Me’phaa indigenous heritage who learned to write in prison. Instead of an autobiography, we propose reading the text as a "sorography," a concept that allows us to understand the writing of the Hermanas as an example of a different narrative form that emerges from a relational, affective, horizontal, and decolonial feminist process that, in Leo’s case, also leads to artisanal forms of restorative justice.